Russian and International Experience of Working with Personality Developing Inquiry - Pavel D. Rabinovich; Mikhail E. Kushnir; Kirill E. Zavedensky; Lidia V. Kremneva; Igor S. Tsarkov (National Research Mordova State University, 2021)
Introduction. Response to challenges of actual mass demand for personalisation of education is not feasible without specification of idea, models and mechanisms of usage of "learning inquiry", which are determined by regional, cultural, social, and historical specifics of society. Relevance of the research is based on the necessity to clarify the term "learning inquiry" to facilitate practical implementation of mechanisms of personal educational logistic realised in digital environment. The article's objective is to present results of analysis of local and international interpretations of the term "learning inquiry" (or its equivalent) as well as practices of its formation and usage. Materials and Methods. Local and global practices (formalised education, family education, "alternative" education) have been analysed with a searching depth of 5-8 years. Searching requests: educational inquiry, personal(sized) learning inquiry, personalized education, personalized learning, student-initiated learning, selflearning, etc. The following concepts have been reviewed: subjectivity, individualisation, personalization, personification, choice theories by D. Leontiev, intermediate action theory by B. Elkonin, theory of complicated systems and personality by K. Rogers, field theory by K. Levin, concept of deep knowledge by K. Duek, etc.; models and practices of active learning based on subjective position of a student. Results. Specifics of terminology related to personalized education are determined and described. A preterm "learning request" has been introduced via system of basic principles of creation of "learning inquiry" model. It has been shown that "learning inquiry" is realized via various educational institutions. In digital environment "learning inquiry" becomes a trigger for transformation towards educational logistic. Discussion and Conclusion. Research results contribute to development of practices of construction of position by participants of educational activity, to practices of work with learning inquiry, to enable to develop mechanisms of transformation towards personal educational logistic and, therefore, to facilitate readiness of educational systems to realisation of personalized education.